Perbandingan Waktu Tunggu Dan Waktu Pelayanan Sistem Pembayaran Cash Dan Cashless Di Parkiran Menggunakan Discrete Event Simulation - Dzulkifli; Aldyth Kendra Azaria; Mohamad Jihan Shofa (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Congestion can take a lot of time for people. Congestion does not only occur on roads but also occurs in public facilities such as parking facilities. where one of the causes is the queue in and out of parking in the business area, which has an impact on discomfort. The purpose of this study was to assess the effectiveness of the cash and non-cash payment service queuing system in terms of waiting time and service time. The stages of the research are observation, data collection on service time, data sampling, data processing and analysis using the discrete event simulation (DES) approach, validation, and suggestions for improvement. The results of the analysis show that the payment system with the cashless method is more effective than the cash payment method. Therefore, the cashless method can be used as a reference for parking service providers in the modern market to be implemented in a parking payment system, with an average service time of the Cashless method of 15.2365 seconds compared to an average service time of the cash method of 42.6812 seconds. seconds or an increase in server time from cash to cashless by 2.81% and a decrease in waiting time using cashless compared to cash by 9.31%. Keywords: Discrete Event Simulation, payment method cashless, Queue System